2020
DOI: 10.1161/circresaha.120.315929
|View full text |Cite
|
Sign up to set email alerts
|

BET Epigenetic Reader Proteins in Cardiovascular Transcriptional Programs

Abstract: Epigenetic mechanisms involve the placing (writing) or removal (erasing) of histone modifications that allow heterochromatin to transition to the open, activated euchromatin state necessary for transcription. A third, less studied epigenetic pathway involves the reading of these specific histone marks once placed. The BETs (bromodomain and extraterminal-containing protein family), which includes BRD2, BRD3, and BRD4 and the testis-restricted BRDT, are epigenetic reader proteins that bind to specific acetylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 156 publications
3
86
0
3
Order By: Relevance
“…From a functional/structural perspective, BRD4 is dubbed a "Swiss army knife" (30). Its two bromodomains "dock" the BRD4-organized regulatory complex (including TFs and cis-regulators) to specific bookmarked chromatin sites, with its C-terminal domain promoting transcriptional activation by interacting with the transcription elongation factor that in turn activates the RNA polymerase II (31). BRD4 was very recently found to possess intrinsic kinase (32) and acetyl transferase activities (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a functional/structural perspective, BRD4 is dubbed a "Swiss army knife" (30). Its two bromodomains "dock" the BRD4-organized regulatory complex (including TFs and cis-regulators) to specific bookmarked chromatin sites, with its C-terminal domain promoting transcriptional activation by interacting with the transcription elongation factor that in turn activates the RNA polymerase II (31). BRD4 was very recently found to possess intrinsic kinase (32) and acetyl transferase activities (33).…”
Section: Discussionmentioning
confidence: 99%
“…Inasmuch as BRD2 lacks a C-terminal domain and its bromodomain sequences are different from that of BRD4 (20), our results may implicate a BET mechanism distinct from that of BRD4. Given limited information about BRD2 functional mechanisms (31), future studies are needed to elucidate the molecular workings that underlie BRD2dominated regulation of S2R transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the BRD4 inhibitor RVX-208 (now called apabetalone) showed potent effect in increasing apolipoprotein A-I and HDL levels/particles and reducing AS (McLure et al, 2013;Jahagirdar et al, 2014;Gilham et al, 2016;Ghosh et al, 2017), and has been tested in clinical trials (Nicholls et al, 2016(Nicholls et al, , 2018Shishikura et al, 2019). Pooling completed phase 2 trial data that suggested its clinical benefits on reducing major adverse cardiovascular events in treated patients (Borck et al, 2020). However, a phase III trial (BETonMACE) completed recently showed that addition of RVX 208 to contemporary standard of care for acute coronary syndrome (ACS) did not significantly reduce major adverse cardiovascular events in patients with a recent (7-90 days) ACS, type 2 diabetes, and low HDL cholesterol (Ray et al, 2020).…”
Section: Potential Combination Of Brd4 Inhibitors With Hdac Inhibitorsmentioning
confidence: 99%
“…Therefore, in the pursuit of new interventional paradigms, it is important to interpret the IH pathogenic mechanisms from an epigenetic perspective. However, epigenetic determinants of SMC state transitions only begin to be unveiled 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…This action involves multiple factors such as the elongation factor complex and central machinery of transcription. It remains poorly understood how BRD4, a seeming global regulator, assumes its functional specificity in different cell types and microenvironments 2 . Transcription factors (TFs) and enhancers are thought to confer BRD4 some gene loci specificity in the genomic landscape 6,7 .…”
Section: Introductionmentioning
confidence: 99%